2022
DOI: 10.1097/bor.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, predictive and prognostic biomarkers in systemic lupus erythematosus: current insights

Abstract: Purpose of reviewBiomarkers for diagnosis, monitoring and prognosis still constitute an unmet need for systemic lupus erythematosus (SLE). Focusing on recent findings, this review summarises the current landscape of biomarkers in lupus. Recent findingsUrine activated leukocyte cell adhesion molecule (ALCAM) exhibited good diagnostic ability in SLE and lupus nephritis (LN) whereas cerebrospinal fluid neutrophil gelatinase-associated lipocalin (NGAL) showed promise in neuropsychiatric SLE. Urine ALCAM, CD163 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…We found that the usCD163 level and usCD163/creatinine ratio were also correlated with the SLEDAI-2K score and anti-ds DNA Ab level. Serum-soluble CD163 ( 29 ), monocyte chemoattractant protein-1 (MCP-1), neutrophil gelatinase-associated lipocalin (NGAL), TNF-like weak inducer of apoptosis (TWEAK), and vascular cell adhesion molecule-1 (VCAM) are new biomarkers of SLE disease activity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the usCD163 level and usCD163/creatinine ratio were also correlated with the SLEDAI-2K score and anti-ds DNA Ab level. Serum-soluble CD163 ( 29 ), monocyte chemoattractant protein-1 (MCP-1), neutrophil gelatinase-associated lipocalin (NGAL), TNF-like weak inducer of apoptosis (TWEAK), and vascular cell adhesion molecule-1 (VCAM) are new biomarkers of SLE disease activity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, data reported in this study should be considered specific to the used measurement method and sample matrix, i.e., EDTA-plasma. An improvement of harmonization in the measurement of circulating calprotectin could highlight the real value of this marker in COVID-19 as well as in other inflammatory diseases, such as autoimmune diseases [ 30 , 31 ] and atherosclerosis-based cardiovascular diseases [ 32 , 33 , 34 ]. Another point that should be addressed to improve the adoption of calprotectin in routine analyses is related to the timing of calprotectin increase before the worsening of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disease remission rate is still not where we want to see it, although the overall rate of SLE patients who have achieved and maintained remission status has improved considerably over recent decades, and further evidence is required to better characterize the pathogenesis and features of SLE, especially in patients in the Asia Pacific region [ 16 , 17 ]. Discovery of new biomarkers of SLE has always been positive, as it can provide better comprehension of SLE pathogenesis and could also be a potential treatment target, for example, CD163, which has been a hot topic lately [ 18 , 19 ]. Nevertheless, this seems to provide limited value to our clinical decisions and treatment, although it would indeed add more benefit in choosing study topics and developing novel treatment targets.…”
Section: Discussionmentioning
confidence: 99%